Re-Interpretation of Makkiyah Verses to Improve Moral Guidance: A Case Study of Flexing Attitudes in The Review of The Tafsir Kemenag - Nadia Alisyia Nuri; Kharis Nugroho; Yeti Dahliana; Andri Nirwana AN (al-Afkar, Journal For Islamic Studies, 2025)
This study examines the prevalent social phenomenon of "flexing," where individuals publicly display wealth, achievements, or personal relationships. This behavior, commonly seen both offline and on social media, is analyzed through the lens of Islamic teachings, particularly the Makkiyah Verses of the Qur'an. By examining verses from surahs such as Al-A'raf, Al-Isra, Al-Kahfi, and Al-Furqan, the study identifies moral guidance that encourages humility, simplicity, and moderation—values often contradicted by flexing attitudes. Through a thematic analysis of these verses, supported by the interpretation of the Ministry of Religion (Kemenag), the research highlights how these teachings can serve as a framework for addressing the cultural shift towards excessive self-promotion and consumerism. This qualitative library research approach aims to contextualize Qur'anic moral principles as a counter to societal behaviors that may foster envy, pride, or social imbalance. Ultimately, the study advocates for the reinforcement of modesty and gratitude, aiming to provide a religious and moral perspective on flexing as a modern cultural trend, demonstrating the ongoing relevance of Qur'anic ethics in addressing contemporary social issues. The findings contribute to understanding the role of Islamic teachings in guiding personal conduct and promoting social harmony in the face of materialistic pressures.